Royalty Payment Responsibility in Commercial Music Concerts: A Juridical Analysis of Jakarta Central Commercial Court Decision Number 92/Pdt.Sus-HKI/Cipta/2024 - Vani Angelina Wilberth; Siti Ngaisah (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2026)
The commercial music concert industry in Indonesia involves complex legal relationships among creators, performing artists, and concert organizers, particularly with respect to the obligation to pay music performance royalties. This study examines the legal framework governing royalty payment responsibility under Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021 concerning the Management of Song and/or Music Copyright Royalties, and critically evaluates the conformity of Jakarta Central Commercial Court Decision Number 92/Pdt.Sus-HKI/Cipta/2024/PN Niaga Jkt.Pst with those instruments. The study employs a normative juridical method with statutory and case approaches, drawing on primary legal materials and Scopus-indexed secondary sources. The findings indicate that the applicable regulatory framework unambiguously places royalty payment obligations on the concert organizer as the commercial user of copyrighted musical works, not on the performing artist whose remuneration constitutes a service fee rather than proceeds from commercial exploitation. The court's imposition of royalty liability on the singer departs from this statutory scheme, mischaracterizes the legal nature of the performance fee, and undermines the collective management mechanism established under the Copyright Act. This study concludes that judicial clarification, regulatory refinement, and stronger enforcement of pre-event licensing compliance are necessary to restore legal certainty and protect creators' economic rights within Indonesia's music industry.